Understanding the mental health impacts of poor quality private-rented housing during the UK's first COVID-19 lockdown. (November 2022) - Newton, Dillon; Lucock, Michael; Armitage, Rachel; Monchuk, Leanne; Brown, Philip
Abstract: This paper examines the mental health impacts of poor quality private-rented housing in the north of England during the UK's first COVID-19 lockdown. The paper draws on data collected from semi-structured telephone interviews with 40 renters in the private-rented sector. We use the Power Threat Meaning Framework to highlight how substandard housing was a social and material vulnerability which, underpinned by powerlessness, resulted in threats that created and exacerbated the mental-ill health of precarious private renters. The paper suggests the pandemic and increased time spent in unhealthy places of residence can create stresses at a time of broader structural fragility, and calls for the greater engagement and integration of health practitioners in the future development of housing policy at all levels. Highlights: Explores mental health impacts of COVID-19 lockdown for private renters in poor quality and precarious housing. Stresses of private-rented housing were 'social and material vulnerabilities' that contributed to mental ill-health. Calls for engagement of health practitioners in developing future housing policy as part of a preventative health system.